Spontaneous Spinal Epidural Hematoma in an Infant. Issue 8 (August 2020) - Kim, Michael; Hoffman, Jessa; Amin, Anubhav; Purohit, Manish; Mohan, Avinash
Abstract : Abstract: A spontaneous spinal epidural hematoma is a collection of blood in the spinal epidural space that occurs in the absence of trauma. They most commonly present in the fourth to fifth decade in life with acute onset neck or back pain with delayed neurologic deficit. However, this presentation is often complicated in children because of the limitations in the pediatric neurologic exam. Magnetic resonance imaging is the imaging modality of choice for diagnosis. Here is a rare case of an infant spontaneous spinal epidural hematoma whose diagnosis was delayed because of a recent history of fever and viral pharyngitis before his development of neurologic deficits. Spontaneous spinal epidural hematomas are a rare phenomenon, which often present with nonspecific symptoms in the pediatric population. This diagnosis should be considered to initiate treatment in a timely manner. The treatment typically is emergent surgical decompression to minimize the risk of permanent neurologic deficit.